TUKANG RABAB DAN KABA RABAB PASISIA DALAM ACARA BARALEK DI NAGARI TALAO - Maiben alpandi; Mistortoify, Zulkarnain (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2024)
The study "Tukang Rabab dan Kaba Rabab Pasisia dalam Acara Baralek di Nagari Talao, Sumatra Barat" explores the competencies and presentation of kaba rabab pasisia in baralek events. This performance reveals the richness of Minangkabau culture, from a warm opening to a meaningful core story. Through poetic lyrics and captivating music, Kaba enriches understanding of Minangkabau cultural values. Tukang Rabab, as cultural guardians, adeptly perform rabab pasisia and master Minangkabau language and literature. Social interaction is key to their competence, living within the community of rabab pasisia artists and exchanging knowledge and skills. Despite facing modernization challenges, the art of rabab pasisia remains relevant and valuable. The participation of tukang rabab in cultural events, art training, and preservation projects strengthens Minangkabau identity and cultural heritage. This performance fosters community solidarity and serves as a platform for learning life values, enriching and preserving Minangkabau cultural identity, and encouraging the younger generation to uphold ancestral traditions